Usual and Written Law in the Russian State of the Early Modern Era: The Problem of Correlation - Arutyunyan, Radmila E.; Dovgyalo, Valeriy K.; Penskaya, Tat’yana M.; Procenko, Evgenij D.; Rasskazov, Vyacheslav L. (Journal of History Culture and Art Research, 2018)
The article deals with the problems associated with the peculiarities of Russian state legal system development during the early modern era. The authors focused on the correlation of oral legal tradition, which forms the basis of customary law, and written, codified law. The Russian historical and legal literature devoted to the legal system development and the development of law in the Russian state at the end of the 15th and 16th centuries, noted long ago that the Code of Laws by Ivan III and Ivan IV, considered as all-Russian legal codes, had very limited circulation in practice, apparently, despite all their significance as the monuments of the Grand Duke’s right. Having ascertained the fact of limited application of grand prince’s judiciary rules, both lawyers and a historian refused to explain this incident. The main attention was paid to the study of the judiciary significance in the context of the legal and judicial system of the centralized Russian state development, but there are no issues related to the specific application of judiciary rules. Proceeding from the thesis put forward by G. Koenigsberger on the "composite nature" of early modern states, the authors of the article explain this legal phenomenon by the fact that the supreme power was compelled to reckon with the interests of local elites and preserve their traditional privileges, including the ones in the legal sphere, in exchange for their loyalty, on the one hand. Hence the limitation of law rules application developed and sanctioned by the supreme authority. On the other hand, the authors proceed from the premise that the "law" in the period under consideration did not have that binding force yet, as it has today, and judicial cases were considered primarily from the point of view of "truth," "justice," and "case specifics". Finally, the authors of the article attribute the "gap" between written law and custom to the "non-written" nature of medieval Russian society in a certain degree and its deep traditionalism, which led to a long-term preservation of "cultural" status but not an own legal status for the written law.